Techniques for Repairing Tegmen Defects When the Ossicles Protrude Above the Floor of the Middle Fossa - Kosarchuk, Jacob; Majid, Maria; Ho, Sydney; Noonan, Kathryn; Sillman, Jonathon; Heilman, Carl (Journal of Neurological Surgery Reports, 2025)
Occasionally, repair of tegmen defects can be complicated by the ossicular chain protruding above the floor of the middle fossa, which traditionally requires disarticulation and reconstruction of the ossicles to manage. This manuscript describes modifications of previously described techniques to address this surgical problem.Case series.In this case series we present three patients with tegmen defect and encephalocele where the ossicles protruded over the floor of the middle fossa. In one instance, a “manhole cover” was created by concentrically layering hydroxyapatite cement around the tegmen defect and placing a piece of calvarium harvested from the bone flap over the defect. In another case, a “bony igloo” was drilled into harvested bone flap and placed over the defect, effectively creating a neo-epitympanum.Hearing preservation, CSF leak recurrence.No patients had recurrence of their encephalocele and/or CSF leak. No patients required manipulation of the ossicular chain intraoperatively. Hearing returned to normal in one case. Hearing worsened in one case, thought to be related to injury to the inner hair cells of the cochlear or cochlear nerve. Hearing did worsen in another case, thought to be related to pneumolabyrinth.The “manhole cover” and “bony igloo” techniques are pragmatic solutions to this rare but complex surgical problem.
Keywords: encephalocele; CSF leak; tegmen; middle fossa; mastoidectomy